Response to: Limberg Flap Reconstruction in Treating Sacrococcygeal Pilonidal Sinus - Hayati, Firdaus; Rahim, Syed Sharizman Syed Abdul; Ani, Mohd Firdaus Che; Zakaria, Andee Dzulkarnaen (Bangladesh Journal of Medical Science, 2020)
Abstract not available Bangladesh Journal of Medical Science Vol.19(2) 2020 p.343-344